The Role Of Public Relations In Increasing Public Awareness Of Health Programs And Hospital Services - Sylvia Sumitro (Jurnal Indonesia Sosial Teknologi, 2023)
Introducing health programs and services provided by hospitals is essential in meeting the community's health needs. This study aims to analyze the role of public relations in increasing public awareness of health programs and hospital services. This research uses qualitative research methods. The data collection technique was carried out by literature study by reviewing the literature relevant to the research. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation, and conclusion drawing. The results showed that public relations is essential in increasing public awareness of health programs and hospital services. Public relations plays a role in increasing public awareness in various ways, including by delivering information and education about health, building public trust in health programs and hospital services, increasing public understanding of the benefits of health programs and hospital services, and encouraging the community to get involved in health programs and hospital services